(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
As a result of the drying up of the Aral Sea, various types of salt and dust are causing serious damage to the Lower Amudarya district and its surrounding areas. The article contains brief information about the methods of reducing the negative effects of various types of harmful salts rising from the Aral Sea.